A Comparison of Caffeine Intake and Physical Activity According to Fatigue Severity in University Students. Issue 1 (March 2023) - Güneş, Musa; Demirer, Büşra
This study aims to compare caffeine intake and physical activity levels in university students with severe and ineffective fatigue and examine the relationship between them. A total of 647 (F:527; M:120) university students were included in this cross-sectional study. Individuals' socio-demographic information, severity of fatigue (Fatigue Severity Scale (FSS)), amount of caffeine intake and physical activity level (International Physical Activity Questionnaire-Short Form (IPAQ-SF)) were evaluated. It was determined that 56.5% of the university students (age: 21.21 ± 2.57) participating in the study had severe fatigue. Caffeine intake and physical activity level of students with severe fatigue were statistically significantly lower than those with ineffective fatigue ( p < 0.05). In addition, there was a weak negative correlation between fatigue and caffeine intake (r = −0.157; p < 0.001) and physical activity level (r = −0.096; p < 0.017). There was a significant positive correlation between caffeine intake and physical activity (r = 0.143; p < 0.001). This study showed that a significant portion of university students have severe fatigue. In addition, individuals with severe fatigue have decreased caffeine intake and lower physical activity levels. To reduce fatigue, caffeine intake in safe doses should be encouraged in accordance with the individual's metabolic and physiological parameters. In addition, physical activity counseling should be given to encourage physical activity.